Nicotine self-administration and ERK signaling are altered in RasGRF2 knockout mice - Morella, Ilaria; Pohořalá, Veronika; Calpe-López, Claudia; Brambilla, Riccardo; Spanagel, Rainer; Bernardi, Rick E. (Frontiers in pharmacology, 2022)
Ras/Raf/MEK/ERK (Ras-ERK) signaling has been demonstrated to play a role in the effects of drugs of abuse such as cocaine and alcohol, but has not been extensively examined in nicotine-related reward behaviors. We examined the role of Ras Guanine Nucleotide Releasing Factor 2 (RasGRF2), an upstream mediator of the Ras-ERK signaling pathway, on nicotine self-administration (SA) in RasGRF2 KO and WT mice. We first demonstrated that acute nicotine exposure (0.4 mg/kg) resulted in an increase in phosphorylated ERK1/2 (pERK1/2) in the striatum, consistent with previous reports. We also demonstrated that increases in pERK1/2 resulting from acute (0.4 mg/kg) and repeated (0.4 mg/kg, 10 daily injections) exposure to nicotine in WT mice were not present in RasGRF2 KO mice, confirming that RasGRF2 at least partly regulates the activity of the Ras-ERK signaling pathway following nicotine exposure. We then performed intravenous nicotine SA (0.03 mg/kg/infusion for 10 days) in RasGRF2 KO and WT mice. Consistent with a previous report using cocaine SA, RasGRF2 KO mice demonstrated an increase in nicotine SA relative to WT controls. These findings suggest a role for RasGRF2 in the reinforcing effects of nicotine, and implicate the Ras-ERK signaling pathway as a common mediator of the response to drugs of abuse.